2015
DOI: 10.2172/1169778
|View full text |Cite
|
Sign up to set email alerts
|

Reference Model 5 (RM5): Oscillating Surge Wave Energy Converter

Abstract: This report is an addendum to SAND2013-9040: Methodology for Design and Economic Analysis of Marine Energy Conversion (MEC) Technologies. This report describes an oscillating surge wave energy converter (OSWEC) reference model design and complements Reference Models 1-4 in the above report.A conceptual design for a taut, moored OSWEC was developed. The design had an annual electrical power of 108 kilowatts (kW), rated power of 360 kW, and intended deployment at water depths between 50 m and 100 m. The study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…A range of costs was given (Copping and Geerlofs [4]) as an acknowledgement of the large amount of uncertainty in their calculations. [16]) describes an oscillating surge wave energy converter (WEC) and RM-6 (Bull et al [17]) an oscillating water column energy converter.…”
Section: Comparing Actual Project Data To Reference Modelsmentioning
confidence: 99%
“…A range of costs was given (Copping and Geerlofs [4]) as an acknowledgement of the large amount of uncertainty in their calculations. [16]) describes an oscillating surge wave energy converter (WEC) and RM-6 (Bull et al [17]) an oscillating water column energy converter.…”
Section: Comparing Actual Project Data To Reference Modelsmentioning
confidence: 99%
“…However, as there has been a limited amount of actual WEC deployment to date, the power matrices used in this study were a mixture of those obtained through real-sea testing (at a larger scale), tank testing (at a smaller scale), and realistic numerical models. In total, the performance of 15 WECs was analysed, including those from [30][31][32][33][34] and WECs in the WES development program (further details cannot be included for confidentiality reasons). Analysis of these data showed that the relationship between mean power and scale depends on the WEC type, relating to the shape of the device and how it extracts energy from the incoming waves.…”
Section: State Of the Art Mean Powermentioning
confidence: 99%
“…The CapEx and OpEx estimates for the WPDS are scaled values from the DOE Marine and Hydrokinetic Reference Model 5 (RM5) design [12], which is a floating OSWEC with similar characteristics, except for the foundation. The OSWEC that was simulated in this analysis has a narrower flap width than what was designed for RM5 (18 m vs. 25 m), and therefore the structural costs have been scaled linearly by a factor of 0.72.…”
Section: Economic Model Inputsmentioning
confidence: 99%